B-spline finite element approach for the analysis of thin-walled beam structures based on 1D refined theories using Carrera unified formulation. (September 2018) - Alesadi, Amirhadi; Ghazanfari, Sarah; Shojaee, Saeed
Abstract: In the current study, 1D refined beam theories on the basis of Carrera Unified Formulation (CUF) are combined with Isogeometric approach (IGA) for the static and free vibration analysis of thin-walled beam structures. The B-spline basis functions utilized in IGA are employed to approximate displacement field due to their interesting attributes in analysis. N-Order Taylor-like expansions are utilized in the framework of CUF which presents finite element matrices in the form of fundamental nuclei that is independent of the type and order of expansion. Higher-order B-spline basis functions attenuate the effect of shear locking properly and higher-order theories presented by CUF are free from Poisson locking phenomenon and utilizations of shear correction factor. Several numerical results including both solid and thin-walled structures are investigated and it is shown that coupling IGA and CUF ends in a suitable methodology to analyze beam structures. Highlights: B-spline basis functions have been utilized to approximate solution field in conjunction with CUF. The proposed approach facilitates employing higher orders theories. Any order of expansions and also any order of B-spline basis function used to reach suitable results. Higher order NURBS basis functions attenuate the shear locking properly.